2011
DOI: 10.1088/0022-3727/44/6/064005
|View full text |Cite
|
Sign up to set email alerts
|

Electric-field effects on magnetic anisotropy in Pd/Fe/Pd(0 0 1) surface

Abstract: Abstract. Electric-field (EF) effects have been studied on magnetic anisotropy in the metallic surfaces Pt/Fe/Pt(001) and Pd/Fe/Pd(001) by means of the first-principles electronic structure calculation which employs the generalized gradient approximation. The variation of anisotropy energy with respect to the EF is found to be opposite to each other. The modulus rate of the variation is larger by a few factors in the Pt substrate than in the Pd one. These results agree qualitatively well with the available exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…The sign of the VCMA effect is expected to be sensitive to the electronic structures near the interfaces of a FM layer. Especially, the electronic structures of nonmagnetic (NM) layers adjacent to the FM layer can determine the signs of the VCMA effect, which had been demonstrated by first principles calculations in Pt/Fe/Pt and Pd/Fe/Pd structures3738. Therefore, the difference in the ferromagnetic material (CFA and CoFeB) and/or crystal structure (e.g., polycrystalline hcp Ru and single crystalline Ru(023) buffer layers) may be responsible for the discrepancy of the signs.…”
mentioning
confidence: 96%
“…The sign of the VCMA effect is expected to be sensitive to the electronic structures near the interfaces of a FM layer. Especially, the electronic structures of nonmagnetic (NM) layers adjacent to the FM layer can determine the signs of the VCMA effect, which had been demonstrated by first principles calculations in Pt/Fe/Pt and Pd/Fe/Pd structures3738. Therefore, the difference in the ferromagnetic material (CFA and CoFeB) and/or crystal structure (e.g., polycrystalline hcp Ru and single crystalline Ru(023) buffer layers) may be responsible for the discrepancy of the signs.…”
mentioning
confidence: 96%
“…The states of the Pd-rich A and Co-rich B in Fig. 4 were compared around the Fermi level in the band structure because the occupied and unoccupied states around the Fermi level are important [42,44,45,46]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…18 Furthermore, the effect of electric field on magnetic anisotropy energy (MAE) has been studied for Fe monolayers on Pd(001) and Pt(001) surfaces, and it has been found that the magnetic anisotropy energy depends linearly on the electric field. 19 The enhancement of magnetic anisotropy in Pt/Fe/Pt(001) is found to be more pronounced than in Pd/Fe/Pd(001) surface. 19 Now, the question arises, for which nanostructures the above-mentioned effects are more pronounced.…”
Section: Introductionmentioning
confidence: 92%
“…19 The enhancement of magnetic anisotropy in Pt/Fe/Pt(001) is found to be more pronounced than in Pd/Fe/Pd(001) surface. 19 Now, the question arises, for which nanostructures the above-mentioned effects are more pronounced. In the present paper, we use first-principle calculations to investigate the magneto-electric effect of Fe chains on Pt(001) as shown in Fig.…”
Section: Introductionmentioning
confidence: 92%